Inhibition of the TNF-α-Induced Serine Phosphorylation of IRS-1 at 636/639 by AICAR - Tomohito Shibata; Akira Takaguri; Kazuo Ichihara; Kumi Satoh (Elsevier, 2013)
AMP-activated protein kinase (AMPK) contributes to the acceleration of insulin signaling. However, the mechanism by which AMPK regulates insulin signaling remains unclear. Serine phosphorylation of insulin receptor substrate (IRS)-1 negatively regulates insulin signaling. Here we investigated the role of AMPK in serine phosphorylation of IRS-1 at 636/639 and 307, which is induced by tumor necrosis factor (TNF)-α in 3T3L1 adipocytes. We demonstrated that the AMPK activator 5-aminoimidazole-4-carboxamide-1-d-ribofuranoside (AICAR) significantly inhibited the TNF-α-induced serine phosphorylation of IRS-1 at 636/639 and 307 by suppression of extracellular signal-regulated kinase (ERK) phosphorylation but not c-Jun-NH2-terminal kinase (JNK) phosphorylation. In addition, AICAR stimulation resulted in enhanced interaction between ERK and MAP kinase phosphatase-4 (DUSP9/MKP-4) without affecting DUSP9/MPK4 mRNA synthesis. Moreover, intraperitoneal administration (0.25 g/kg) of AICAR to db/db mice improved blood glucose levels and inhibited the phosphorylation of ERK in adipose tissue. In conclusion, we propose a new mechanism in which AICAR suppresses TNF-α-induced serine phosphorylation of IRS-1 at 636/639 and 307 by enhancing the interaction between ERK and DUSP9/MKP-4. Taken together, these findings provide evidence that AMPK plays a crucial role in improving of type 2 diabetes. Keywords:: 3T3L1 adipocyte, AICAR, insulin receptor substrate (IRS)-1, DUSP9/MKP-4, insulin resistance